2021
DOI: 10.1101/2021.09.20.21263830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term low-dose acetylsalicylic use shows protective potential for the development of both vascular dementia and Alzheimer’s disease in patients with coronary heart disease but not in other individuals from the general population: results from two large cohort studies

Abstract: Objectives: To investigate the association between long term low-dose acetylsalicylic acid (LDASA) use and the development of all-cause dementia, Alzheimer's disease (AD) and vascular dementia (VD). Design: Meta-analysis of individual participant data from two prospective cohort studies. Setting: Community-dwelling older adults from Germany (ESTHER) and United Kingdom (UK Biobank). Participants: 5,258 ESTHER and 305,394 UK Biobank participants who were 55 years or older and completed drug assessment were i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis published in May 2022 found that subjects with pre-existing CAD who took low-dose aspirin had significantly lower rates of AD and VD compared to those who did not [ 185 , 186 , 187 ]. However, the use of antiplatelet therapy on cognition has not been studied specifically in the post-AMI population, likely due to the key role of antiplatelet therapy in AMI management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis published in May 2022 found that subjects with pre-existing CAD who took low-dose aspirin had significantly lower rates of AD and VD compared to those who did not [ 185 , 186 , 187 ]. However, the use of antiplatelet therapy on cognition has not been studied specifically in the post-AMI population, likely due to the key role of antiplatelet therapy in AMI management.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited placebo-controlled trials regarding antiplatelet use in VD, as the diagnosis of VD is based on a history of cardiovascular risk factors, stroke or AMI, with patients likely to already be on an antiplatelet. One randomised controlled trial, multiple cohort studies and one systematic review have all concurred that antiplatelet therapy may reduce the risk of VD [ 185 , 187 , 202 ]. A longitudinal study of patients on the South London Stroke Register found that dual antiplatelet therapy (DAPT) significantly reduced rates of cognitive impairment in stroke patients with AF, and another randomised controlled trials reported reduced rates of early neurological deterioration in post-stroke patients on DAPT compared to aspirin alone [ 200 , 203 ].…”
Section: Resultsmentioning
confidence: 99%